2022
DOI: 10.3389/fonc.2022.992509
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modality radiomics nomogram based on DCE-MRI and ultrasound images for benign and malignant breast lesion classification

Abstract: ObjectiveTo develop a multi-modality radiomics nomogram based on DCE-MRI, B-mode ultrasound (BMUS) and strain elastography (SE) images for classifying benign and malignant breast lesions.Material and MethodsIn this retrospective study, 345 breast lesions from 305 patients who underwent DCE-MRI, BMUS and SE examinations were randomly divided into training (n = 241) and testing (n = 104) datasets. Radiomics features were extracted from manually contoured images. The inter-class correlation coefficient (ICC), Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Xinmiao Liu et al. found that combining MRI, B‐mode ultrasound (BMUS), and strain elastography (SE) images improved the accuracy of predicting breast lesion classification to an AUC of 0.941, compared with that of MRI (0.877), BMUS (0.819) and SE (0.880) alone 34 . These studies highlighted the importance of using multi‐modality imaging in radiomic feature analysis to improve the accuracy of predicting treatment responses in patients with head‐and‐neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Xinmiao Liu et al. found that combining MRI, B‐mode ultrasound (BMUS), and strain elastography (SE) images improved the accuracy of predicting breast lesion classification to an AUC of 0.941, compared with that of MRI (0.877), BMUS (0.819) and SE (0.880) alone 34 . These studies highlighted the importance of using multi‐modality imaging in radiomic feature analysis to improve the accuracy of predicting treatment responses in patients with head‐and‐neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the radiomic logistic regression model could noninvasively predict the likelihood of malignancy of breast lesions amenable to breast biopsy. Although in the medical literature many studies are devoted to assessing the possibility of differentiating between benign and malignant lesions for MRI data [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], there are currently no public and widely accepted radiomics-based guidelines for the pre-operative prediction of malignancy likelihood in patients amenable to MR-VABB. Some recent studies have paved the way to a radiomics-driven exploratory research phase [ 33 , 34 ], and much effort should be made to realize translation into clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Liu et al. employed radiomics features extracted from SE images for breast cancer prediction, yielding a Radscore with an AUC of 0.866 in the test set ( 18 ). Besides, Ma et al.…”
Section: Discussionmentioning
confidence: 99%